Elemental Chlorine-Free Bleaching of Soda Pulp Cooked from Rapeseed Straw - Říhová, Martina; Potůček, František (Technická univerzita vo Zvolene, 2016)
Soda pulp cooked from rapeseed straw was subjected to a four-stage elemental chlorine-free bleaching under laboratory conditions. Chlorine dioxide and hydrogen peroxide were used as bleaching chemicals. For comparison, kraft pulp cooked from a blend of spruce and pine was subjected to the same bleaching sequence D0EPD1P. After each bleaching step, the optical and strength properties were measured. The preliminary results showed that bleachability of soda rapeseed pulp was lower in comparison with kraft softwood pulp for D0EPD1P bleaching sequence. The brightness increment of 43.2 % ISO and 48.5 % ISO was achieved for soda and kraft pulps, respectively. However, the bleaching had a negative impact on the zero-span breaking length for both pulps. The brightness attained for elemental chlorine-free bleaching of soda and kraft pulps was compared with that obtained for totally chlorine-free bleaching of kraft softwood pulp in our previous work.
ECF bělení natronové buničiny uvařené z řepkové slámy
Keywords: soda rapeseed pulp; ECF bleaching; brightness; zero-span breaking length; natronová řepková buničina; ECF bělení; bělost; tržná délka vláken